0
$\begingroup$

I need to use the so called Ring Tower Theorem to show that $[\mathbb{Q}(\sqrt2,\sqrt3):\mathbb{Q}]=4$, but I'm quite confused with the notation and some concepts. First of all, my book says that if $a$ in some extension $E$ of $\mathbb{Q}$ is algebraic over $\mathbb{Q}$ then the elements of $\mathbb{Q}(a)$ can be written in the form $p+qa$, with $p,q\in\mathbb{Q}$. Hence we know that, since $\mathbb{Q}(\sqrt2,\sqrt3)=\mathbb{Q}(\sqrt2+\sqrt3)$, elements of $\mathbb{Q}(\sqrt2,\sqrt3)$ can be written in the form $p+(\sqrt2+\sqrt3)q$. But doesn't this imply that the the dimension of the basis for $\mathbb{Q}(\sqrt2,\sqrt3)$ is 2, like it is for $\mathbb{Q}(\sqrt2)$?

The Tower Theorem says that if $E$ is a finite extension field of the field $G$ and $G$ is a finite extension of the field $F$, then $E$ is a finite extension of the $F$, and $[E:F]=[E:G][G:F]$.

If I try to apply this theorem to the case in question, I would do as follows:

$$[\mathbb{Q}(\sqrt2,\sqrt3):\mathbb{Q}]=[\mathbb{Q}(\sqrt2,\sqrt3):\mathbb{Q}(\sqrt2)][\mathbb{Q}(\sqrt2):\mathbb{Q}] $$

So I know that $[\mathbb{Q}(\sqrt2):\mathbb{Q}]=2$, but how do I find $[\mathbb{Q}(\sqrt2,\sqrt3):\mathbb{Q}(\sqrt2)]$?

$\endgroup$
  • 9
    $\begingroup$ It is not true that all elements of $\mathbb Q(a)$ can be written as $p+qa$, you need to include higher powers of $a$ as well. $\endgroup$ – Santiago Canez Mar 24 '17 at 4:11
2
$\begingroup$

(In what follows we assume all fields are subfields of a suitable algebraic closure contained in $\Bbb C$).

Note that $\sqrt{3}$ is a root of $x^2 - 3 \in \Bbb Q(\sqrt{2})[x]$, so if $x^2 - 3$ is irreducible over $\Bbb Q(\sqrt{2})$, we have that $[(\Bbb Q(\sqrt{2}))(\sqrt{3}):\Bbb Q(\sqrt{2})] = 2$, and of course it is not hard to show that:

$\Bbb Q(\sqrt{2},\sqrt{3}) = (\Bbb Q(\sqrt{2}))(\sqrt{3})$, by dual inclusion.

If $x^2 - 3$ is reducible over $\Bbb Q(\sqrt{2})$, this implies that $\sqrt{3} \in \Bbb Q(\sqrt{2})$.

If so, we have $\sqrt{3} = a + b\sqrt{2}$ for some $a,b \in \Bbb Q$. Thus:

$3 = (a + b\sqrt{2})^2 = (a^2 + 2b^2) + (2ab)\sqrt{2}$. Since $\{1,\sqrt{2}\}$ is a $\Bbb Q$-basis of $\Bbb Q(\sqrt{2})$ as a $\Bbb Q$-vector space, this in turn implies:

$a^2 + 2b^2 = 3\\2ab = 0.$

If not both $a,b$ are zero, then either $a = 0$, or $b = 0$. The latter leads to $a^2 = 3$ (and thus $\sqrt{3} \in \Bbb Q$), while the former leads to: $b^2 = \frac{3}{2}$ (and thus $\sqrt{\frac{3}{2}} \in \Bbb Q$), neither of which is possible (why?).

But if both $a,b = 0$, then $0 = 3$. Thus $\sqrt{3} \not\in \Bbb Q(\sqrt{2})$, so that $x^2 - 3$ is irreducible over $\Bbb Q(\sqrt{2})$.

$\endgroup$
2
$\begingroup$

Let $x=\sqrt 2+\sqrt 3$. Then $x-\sqrt 3=\sqrt 2$. So $x^2-2\sqrt 3x+1=0$. But this is not the minimum degree polynomial over $\mathbb{Q}$ since $-2\sqrt 3 \notin\mathbb{Q}$. Thus with $x^2+1=2\sqrt 3x$ squaring both sides gives $x^4-10x^2+1=0$. Hence $[\mathbb{Q}(\sqrt2,\sqrt3):\mathbb{Q}]=4$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.